Retraction Note to: Simulation Study of Dynamic Characteristics of Hot Pepper Harvester - Kang, Seokho; Kim, Junhee; Kim, Yeongsu; Ha, Yushin; Woo, Seungmin (Journal of Biosystems Engineering, 46(3), 2021)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1007/s42853-021-00107-9